2021
DOI: 10.51791/njap.v44i3.758
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for egg production traits in crosses between local and exotic chickens estimated by Bayesian inference

Abstract: Estimates of genetic parameters for economic traits are important to enable the breeder estimate the breeding value of individuals available for selection. Thus, this study was carried out to estimate genetic parameters namely heritability and genetic correlations among egg production traits in two strain crosses using bivariate animal model in Bayesian (MCMC) method. The egg production data were obtained from four generations which comprised the base population of two commercial egg strains and the local chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Heterosis is the favourable departure from additivity in a crossbred population and usually results from directional dominance and increase in heterozygosity among the crossbreds. Works on heterosis in body weight and short term egg production traits between local and exotic chickens have been reported by Omeje (2001, 2005) and Udeh (2011). The authors reported substantial heterosis for body weight and short term egg production (henday rate of production and total egg mass) in the F1 crosses and residual heterosis in the back crosses of local and exotic chickens.…”
Section: Discussionmentioning
confidence: 91%
“…Heterosis is the favourable departure from additivity in a crossbred population and usually results from directional dominance and increase in heterozygosity among the crossbreds. Works on heterosis in body weight and short term egg production traits between local and exotic chickens have been reported by Omeje (2001, 2005) and Udeh (2011). The authors reported substantial heterosis for body weight and short term egg production (henday rate of production and total egg mass) in the F1 crosses and residual heterosis in the back crosses of local and exotic chickens.…”
Section: Discussionmentioning
confidence: 91%